Performance evaluation of IEEE 802.11p, LTE and 5G in connected vehicles for cooperative awareness. Issue 4 (27th October 2021) - Tahir, Muhammad Naeem; Katz, Marcos
Abstract: In recent years, researchers and scientists are continuously striving to design and develop advance wireless technologies for vehicular communication. Advanced short‐range (IEEE‐802.11p/ITS‐G5) and long‐range (LTE, LTE‐A, and 5G) technologies are indispensable for Vehicular Ad hoc networking (VANETs). Meanwhile, exploiting technologies for cooperative awareness of connected vehicles is important for seamless network connectivity in hazardous situations. For seamless network availability, there is a need to integrate short‐range and long‐range technologies together. In this article, we design a pilot platform based on IEEE‐802.11p, LTE and 5G test network (5GTN) utilizing road traffic and weather information. The use of real‐time and accurate road traffic and weather information together with road condition information is crucial to enhance road safety. To deliver updated road weather and traffic information, we have used a combination of networks. In this article, a comparison of vehicle to vehicle (V2V) and vehicle to infrastructure (V2I) pilot scenarios was carried out considering the mentioned networks. The used IEEE 802.11p acts as a primary vehicular communication channel, assisted by other cellular‐based LTE and 5G networks. Network performance was analyzed by considering latency, packet loss, and throughput in V2V and V2I scenarios. These pilot measurements revealed that the state‐of‐the‐art 5G test network performs better in contrast of IEEE‐802.11p and LTE network by delivering real‐time road weather and road traffic observation data. These pilots filed measurements show the potential of combining short‐ and long‐range technologies for enhanced road safety. Abstract : In this article, we have designed a pilot platform based on IEEE‐802.11p, LTE and 5G test network (5GTN) utilizing road traffic and weather information. The use of real‐time and accurate road traffic and weather information together with road condition information is crucial to enhance road safety. These pilots filed measurements show the potential of combining short‐ and long‐range technologies to enhance road safety.